Zanim zabłysło światło wiary Chrystusowej. Słowianie w orbicie wiary i kultury pogańskiej / Before the light of Christ’s faith shone. The Slavs in the orbit of pagan faith and culture - Olga Osadczy; Aleksandra Osadczy-Kępka (Language, Culture, Politics)
The article introduces the currently little popular subject of Slavic mythology, and presents the pantheon of the most important Slavic deities as well as the beliefs, cults and rituals of the Slavs living mainly in the eastern territories. The article is a philological, historical and anthropological analysis of the origins of words, expressions and customs of the names of ancient gods and their influence on contemporary culture and religion, as well as a comparison with the Christian religion. Other monuments, archaeological finds and sources from Slavic and mediaeval times located in the present-day areas of Central and Eastern Europe were also described, their meaning and connection with a particular cult explained, as well as their fate after the Christianisation of Europe.